PENILAIAN PEMBELAJARAN BAHASA INDONESIA DALAM KURIKULUM MERDEKA - Ketut Suar Adnyana (Program Studi Pendidikan Bahasa Indonesia dan Daerah Universitas PGRI Mahadewa Indonesia, 2023)
Efforts to improve the quality of education in Indonesia have been carried out since 2009. The government has fulfilled the education budget obligation of 20% of the State Budget and continues to increase the education budget from IDR 332.4 T in 2013 to IDR 550 T in 2021. However, various indicators of student learning outcomes students have not shown encouraging results. The learning crisis was exacerbated by the covid 19 pandemic. Covid 19 caused learning loss to occur. To anticipate learning loss and learning gaps at the Ministry of Education and Culture (now Kemendikbudristek), the Ministry of Education and Culture issued an emergency curriculum for educational units under special conditions. The use of the emergency curriculum was significantly able to reduce learning-loss indications during the pandemic for both literacy and numeracy achievements. To overcome the potential for learning loss and learning gaps during a pandemic. It is necessary to develop a curriculum that is comprehensively capable of dealing with the learning crisis which is an acute problem in Indonesia. Seeing the various challenges that have occurred, the Ministry of Education, Culture, Research and Technology (Kemendikbudristek) is trying to make efforts to restore learning. One of the efforts made by the Ministry of Education and Culture to overcome the existing problems is implementing the Kurikulum Merdeka (which was previously called the Kurikulum Prototipe). Implementation of the Kurikulum Merdeka requires teachers to understand the essence of the Kurikulum Merdeka include assessment implementation. The assessment carried out functions as a learning process (assessment as learning), for the learning process (assessment for learning), and an assessment at the end of the learning process (assessment of learning). Keywords : kurikulum merdeka, assesment, learning loss, learning gap